A Study on Mindful Learning: Can Mindfulness-Based Social-Emotional Learning Strengthen Student Learning Focus? - Alika Setia Putri; Hendri Ardianto; Ayu Andriyaningsih; Burmansah Burmansah (International Journal of Science and Applied Science: Conference Series, 2024)
This study aims to analyze the effect of Mindfulness-Based Social Emotional Learning (MBSEL) on students' learning focus in private junior high schools. Problems often faced by students include putting their heads on the table when bored, scribbling as a sign of lack of attention, chatting while the teacher is teaching, and using cell phones to check notifications. In addition, less interactive teaching methods also play a role in decreasing learning focus. This study uses a quantitative approach with a survey method. The study population included 140 students, with a sample of 104 students selected using proportional random sampling techniques. Respondents came from grades VII to IX students in the 2024/2025 academic year. The analysis showed a positive and significant effect between MBSEL and students' learning focus, with a tcount value of 8.034 and a significance value of p <0.05. Simple regression produced an R² value of 0.388, indicating that MBSEL contributed 38.8% to increasing students' learning focus, while 61.2% was influenced by other factors not examined in this study. This finding confirms the importance of implementing MBSEL to improve students' learning focus.